1998
DOI: 10.1002/(sici)1521-4141(199802)28:02<488::aid-immu488>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Administration to mouse of endotoxin from gram-negative bacteria leads to activation and apoptosis of T lymphocytes

Abstract: Lipopolysaccharide (LPS) from gramnegative bacteria is a well-known T cell-independent B lymphocyte mitogen and macrophage/monocyte activator. While the conventional view holds that LPS is ignored by T cells, we report here that administration of LPS to mice activates all B cells, but also engages most CD4 and CD8 T cells, as measured by the expression of the activation markers CD69 and CD25 and by size increase. T cells recruited in endotoxin-treated mice showed, following in vitro stimulation by concanavalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
2
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 36 publications
3
32
2
2
Order By: Relevance
“…This is in line with several reports that LPS stimulates murine CD8 1 T activation in vivo via an indirect pathway involving APC [17,18,26]. The reason for the failure of murine CD8 1 T cells, in contrast to human CD8 1 T cells, to respond to LPS is not fully understood.…”
Section: Discussionsupporting
confidence: 79%
“…This is in line with several reports that LPS stimulates murine CD8 1 T activation in vivo via an indirect pathway involving APC [17,18,26]. The reason for the failure of murine CD8 1 T cells, in contrast to human CD8 1 T cells, to respond to LPS is not fully understood.…”
Section: Discussionsupporting
confidence: 79%
“…In the present study, the periarterial lymphatic sheath of the spleen of the LPS group showed aggregation and thinning in shape, with a decrease in the quantity of lymphocytes. The histological changes of spleen demonstrate that the number of T lymphocytes in the inner periarterial lymphatic sheath decreases markedly after LPS injection, which is consistent with the results of previous studies (Groeneveld et al, 1985;Castro et al). The reduction of intrasplenic T cells may be due to the increase of apoptosis which was related to LPS-activated B cells.…”
Section: Discussioncontrasting
confidence: 68%
“…However, Castro and his colleagues have reported that administration of LPS to spleen activated all B cells and most T cells (CD4 and CD8 T cells), and increased the expression of the activation marker CD69. Massive T cells apoptosis was seen following LPS exposure in the spleen (Castro et al, 1998). In the present study, the periarterial lymphatic sheath of the spleen of the LPS group showed aggregation and thinning in shape, with a decrease in the quantity of lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Salmonella spp. were shown to trigger apoptosis of monocyte-macrophages and apoptosis or anergy in T cells, whereas PMN spontaneous apoptosis can be delayed by interaction with the bacteria [219][220][221][222]. Modulation of this mechanism in the cells encountered in the various tissues of the RES may provide an excellent strategy to evade the immune system.…”
Section: Extraintestinal Infection : Interaction With the Reticulo-enmentioning
confidence: 99%